Transforming Islamic religious counselors into agents of mosque-based community economic empowerment in Pesawaran Regency - Asmaria, Asmaria; Noviarita, Heni; Wakhid, Ali Abdul; Setiawati, Rini (Journal of Islamic Economics Lariba, 2026)
IntroductionIslamic religious counselors have traditionally focused on spiritual guidance, yet evolving socio-economic demands have expanded their role into community economic empowerment. Mosques and religious institutions now serve as hubs for entrepreneurship development, sharia-based financial literacy, halal certification assistance, and digital outreach. However, empirical studies examining how this role transformation unfolds at the local level, particularly in Indonesia, remain limited.ObjectivesThis study analyzes the transformation of Islamic religious counselors in Pesawaran Regency into agents of community economic empowerment. It identifies the strategies they employ, the enabling and constraining factors that shape their work, and the wider implications for community welfare, institutional development, and faith-based economic initiatives.MethodUsing a qualitative descriptive design, the study collected data through in-depth interviews, participant observations, and document analysis. Informants included counselors, local religious leaders, microenterprise actors, and community members selected purposively to ensure relevance and depth. Data were analyzed using thematic techniques to capture patterns of practice, challenges, and perceived outcomes.ResultsFindings indicate that counselors have integrated da‘wah with economic facilitation through mosque-based mentoring, financial literacy education, halal certification support, and digital tools. These efforts strengthened business skills, increased market access, and enhanced economic confidence among microenterprises. Structural constraints—such as limited counselor capacity, weak interagency coordination, and insufficient evaluation mechanisms—restricted program scalability, yet community trust and cross-sector partnerships enhanced effectiveness.ImplicationsThe study highlights the potential of counselor-led, mosque-centered empowerment as a culturally grounded model for community development. Strengthening governance, digital capacity, and evaluation systems is essential for sustaining impact and expanding inclusion.Originality/NoveltyThis research provides one of the most detailed qualitative accounts of counselor-led economic empowerment in an Indonesian locality, offering conceptual, practical, and policy insights into the alignment of da‘wah, Islamic economic principles, and community development.